Bioavailability of Rumen-Protected Carnitine in Lactating Dairy Cows - K. Olagaray; J. Shaffer; C. Armendariz; A. Bellamine; S. Jacobs; E. Titgemeyer; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2016)
For this study, 56 lactating Holstein cows (143 ± 72 days in milk) were used in a randomized complete block design to evaluate 2 rumen-protected products compared to crystalline carnitine. Treatments were a) control, b) 3 grams/day crystalline L-carnitine (raw), c) 6 grams/day raw, d) 5 grams/day 40COAT (40% coating, 60% L-carnitine), e) 10 grams/day 40COAT, f) 7.5 grams/day 60COAT (60% coating, 40% L-carnitine), and g) 15 grams/day 60COAT. Treatments were top-dressed to diets twice daily. The 14-day experiment included a 6-day baseline-measurement period with the final 2 days used for data and sample collection and an 8-day treatment period with the final 2 days used for data and sample collection. Plasma, urine, and milk samples were analyzed for L-carnitine. Crystalline (P<0.001) and 40COAT (P = 0.01) linearly increased plasma L-carnitine, and 60COAT tended to linearly increase plasma L-carnitine (P = 0.08). Total daily excretion (milk + urine) of L-carnitine averaged 1.52 ± 0.04 grams in controls, increased linearly with crystalline and 40COAT, and increased quadratically with 60COAT (all P<0.05). Crystalline increased plasma L-carnitine and milk + urine L-carnitine more than 40COAT and 60COAT (all P<0.05). Carnitine supplementation increased carnitine concentrations in plasma, milk, and urine; however, the rumen protection did not provide additional increases in concentration.
Keywords: L-carnitine; bioavailability; dairy cow